A Novel and Fast Purification Method for Nucleoside Transporters - Hao, Zhenyu; Thomsen, Maren; Postis, Vincent L. G.; Lesiuk, Amelia; Sharples, David; Wang, Yingying; Bartlam, Mark; Goldman, Adrian (Frontiers in Molecular Biosciences, 2016)
Nucleoside transporters play critical biological roles in humans, and to understand the molecular mechanism of nucleoside transport requires high-resolution structural information. However, the main bottleneck for structural analysis of nucleoside transporters is the production of pure, stable and high quality native protein for crystallization trials. Here we report a novel membrane protein expression and purification strategy, including construction of a high-yield membrane protein expression vector, and a new and fast purification protocol for nucleoside transporters. The advantages of this strategy are the improved time efficiency, leading to high quality, active, stable membrane proteins, and the efficient use of reagents and consumables. Our strategy might serve as a useful point of reference for investigating nucleoside transporters and other membrane proteins by clarifying the technical points of vector construction and improvements of membrane protein expression and purification.